Polyurethane foams with purine rings - Lubczak, J. (Polimery, 2022)
New group of foams can be obtained from isocyanates, water and polyetherols synthesized from uric acid and alkylene carbonates. Due to the presence of purine rings those polyurethanes are remarkably thermally stable and withstand prolonged heating at temperatures above 200°C. The results of studies on influence of kind of polyetherol and composition subjected to foaming on the properties of polyurethane foams are presented. The thermal stability and mechanical properties of the foams were determined before and after thermal exposure.